2010
DOI: 10.1210/jc.2010-0634
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Thyrotropin-Stimulated Radioiodine Therapy of Nodular Goiter Allows Major Reduction of the Radiation Burden with Retained Efficacy

Abstract: This is the first study to demonstrate that rhTSH not only increases the thyroid 131I uptake, but per se potentiates the effect of 131I-therapy, allowing a major reduction of the 131I-activity without compromising efficacy. This approach is attractive in terms of minimizing posttherapeutic restrictions and in reducing the potential risk of radiation-induced malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 23 publications
1
54
0
1
Order By: Relevance
“…rhTSH in a low single dose increases 131 I uptake by two-to fourfold, and similar therapeutic effects (in comparison with higher 131 I activities without rhTSH prestimulation), and with lower exposure of extrathyroidal tissues to radiation (23 given (11,14,16,19,24,25). Overall, it has been shown that rhTSH doses lower than 0.1 mg do not cause acute increases in TV or thyroid hormone levels (26).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…rhTSH in a low single dose increases 131 I uptake by two-to fourfold, and similar therapeutic effects (in comparison with higher 131 I activities without rhTSH prestimulation), and with lower exposure of extrathyroidal tissues to radiation (23 given (11,14,16,19,24,25). Overall, it has been shown that rhTSH doses lower than 0.1 mg do not cause acute increases in TV or thyroid hormone levels (26).…”
Section: Introductionmentioning
confidence: 84%
“…During the last decade, and based on the above observations, rhTSH has been evaluated as an adjuvant to 131 I therapy, in an attempt to improve the efficacy of this treatment for MNG (18,39,40). Different rhTSH doses have been utilized: in some studies 0.2 mg or more (41,42,43,44,45,46,47), while in others 0.1 mg or less (11,16,20,24,31,48). Since the introduction of rhTSH as an aid for 131 I therapy in MNG, nine randomized controlled trials (RCTs) have been published (11,14,15,16,19,24,25,44,45 reduction of the goiter.…”
Section: Rhtsh and 131 I For Mngmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was part of a double-blind randomized controlled trial, described in detail elsewhere [16]. In brief, 90 patients suffering from compressive nodular goiter were randomized to either rhTSH-stimulated 131 I therapy, aiming at a thyroid irradiation dose of 50 Gy, or placebo-stimulated 131 I therapy, aiming at a thyroid dose of 100 Gy.…”
Section: Methodsmentioning
confidence: 99%
“…Fokozza a mirigy radioszenzitivitását. 100 Gy besugárzási dózissal végzett terá-pia eredménye azonos volt azzal, ha 50 Gy-t adtak rhTSH-előkészítéssel [31]. Előnyösen változik a jódki-netika, emiatt az extrathyreoidealis sugárterhelés csök-ken.…”
Section: Göbös Strúmák Radiojódkezeléseunclassified